Malaysian architects' experiences on performance-based identity and competence in BIM design management - Shahruddin, Syafizal (2022)
The inherited identity and competence of an architect as a natural leader, prime decision maker, and creative designer are destabilised in building information modelling (BIM) design management practices. Yet, the macro-level stakeholders in the Malaysian architecture industry are still debating whether to restore their long-lost identity or transform their core values to remain relevant. The current research focuses mostly on architects' adaptive strategies for negotiating their desired identity rather than on their ability to properly perform their way into a variety of identities in such a context. The latter is more important because it reflects what clients value most when hiring architects: competence, performance, and identity. The researcher, therefore, seeks to investigate the lived experience of an architect demonstrating competence and performing his or her way into identities following the contextual change in BIM design management practices. Drawing upon the interpretive phenomenological research design, the researcher first employed a desk review technique to identify the contextual changes that have triggered the redefinition of architects’ inherited identity and competence demonstration in BIM design management practices. Then, the researcher deployed a written account exercise and an in-depth semistructured interview technique to explore their experiences in demonstrating competence in such an environment. Finally, individual and group member check sessions were conducted to verify their performed identity based on their experiences demonstrating competence following the contextual change in BIM design management. A thematic analysis resulted in the following contextual changes in BIM design management practices: changes in governmental policy, regulatory standards, and guidelines; expanding in the scope of services; changes in project hierarchies and authority structures; changes in organisational structure and culture; changes in everyday architectural work processes; and changes in the division of labour. The analytical approaches of naïve reading and thematic analysis also revealed that the architects demonstrated their competence by applying the constructability, buildability, and fire safety measures knowledge in developing BIM models; contextualising BIM terminologies into the existing local industry workflows; dictating the organisational culture; managing personal and team adversity professionally; anticipating the future market; managing the workforce planning; and developing the tool ecologies, to name a few within and across the organisational settings. Finally, individual and group member check sessions resulted in the following seven performed identities: “performing more of a design strategist”, “performing more of a design translator”, “performing more of a design facilitator”, “reinstating the identity as a design coordinator”, “performing more of a design curator”, “performing more of a design innovator”, and “performing more of a design entrepreneur”. This study contributed to knowledge on three levels: the framework of contextual changes in BIM design management practices, the BIM competence demonstration framework for architects, and the performance-based identity framework of an architect in BIM design management practices. This study could facilitate the Malaysian Institute of Architects (PAM) to restructure continuing professional development (CPD) programmes and reform the standard competence framework to promote architect identity hybridisation and associated competencies in the environment.